2019
DOI: 10.1111/pim.12677
|View full text |Cite
|
Sign up to set email alerts
|

Th2 signals are not essential for the anti‐arthritic effects of Trichinella spiralis in mice

Abstract: Aims Many parasitic helminths are known to alter host immune responses and consequently affect the progression of autoimmune and allergic diseases. The parasitic nematode Trichinella sp has been reported to suppress several experimental diseases in rodents, including experimental autoimmune encephalomyelitis, type 1 diabetes, colitis, airway inflammation and autoimmune arthritis. We tried to clarify requirement of Th2 cytokines in the anti‐arthritic effects of Trichinella spiralis (Ts) against collagen‐induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…We also observed significant impairment of anti‐IIC IgG production by Py infection (Figure 3). Taken together with the similar observation in helminth infections, 7,11 the impairment of humoral immunity in CIA may be a widely observed phenomenon among various parasites.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…We also observed significant impairment of anti‐IIC IgG production by Py infection (Figure 3). Taken together with the similar observation in helminth infections, 7,11 the impairment of humoral immunity in CIA may be a widely observed phenomenon among various parasites.…”
Section: Discussionsupporting
confidence: 60%
“…mansoni , 10 but did not abolish alleviation via T . spiralis 11 . Thus, Th2‐biased cytokine alteration is not always essential for the suppression of arthritis by helminths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is well known that the major extrinsic driver of eosinophil expansion was helminth infection. Numerous previous studies in experimental mouse models have demonstrated clinical improvement of inflammatory activity in a variety of autoimmune and inflammatory diseases including RA (7,(62)(63)(64)(65)(66)(67). These observations led to the proposal that harness helminth and their secreted products would represent a promising interventional approach for the treatment of RA, as supported by the findings that a filarial nematode-derived glycoprotein, ES-62, has been proved to exert an anti-inflammatory and anti-osteoclastogenic effect in mouse arthritis models (68)(69)(70)(71).…”
Section: Future Perspective In Therapymentioning
confidence: 90%
“…Trichinella spiralis alleviated arthritis in CIA model through STAT6 independent mechanism (Osada et al, 2020).…”
Section: Autoimmune Diseases and Parasitic Infections: Rheumatoid Art...mentioning
confidence: 99%